Integrated reporting : a new accounting disclosure - Mio, Chiara (Palgrave Macmillan, 2016)
This book is a timely addition to the fast-growing international debate on Integrated Reporting, which offers a holistic view of the evolution and practice of Integrated Reporting. The book covers the determinants and consequences of Integrated Reporting, as well as examining some of the most relevant issues (particularly in the context of the United States) in the debate about Integrated Reporting. The authors address key topics relating to Integrated Reporting such as: the extent to which consistency between integrated and other company reporting can be achieved, and the fundamental role of integrated thinking within a company setting. More specifically, the book provides a detailed discussion about the role of institutional investors, corporate governance systems and cultural variables in the practice of Integrated Reporting. The book contextualises Integrated Reporting as a practice within the broader realm of international accounting standards, with insight into its impact upon global markets.- Resumé vydavatel